Field day - Butterworth, Nick.; Inkpen, Mick. (New York : Bantam, 1993)
Parents and children participate in the Field Day races.
School Library Journal.
Grades 1 and 2.
2.6
K-3
Keywords: Racing -- Fiction; Track athletics -- Fiction